The significance of retroflexion technique in the right colon on adenoma detection rates during colonoscopy - Shahawy,Mohamed S. EL (2019)
ABSTRACT Background and aim: Right colon adenomas can easily missed with significant adenoma miss rate particularly when they are located behind the haustral folds and anatomical flexures. The aim of this study was to assess the significance of retroflexion technique in the right colon for improving adenoma detection rates compared with forward-view technique. Methods: A total of 200 patients scheduled for elective colonoscopy were recruited. During the standard forward-view examination, the colonoscope was withdrawn from the cecum to the hepatic flexure while under meticulous observation. Subsequently, the cecum was reintubated and the right side of the colon was assessed in the retroflexed-view to the hepatic flexure. The primary outcome of this study was comparison of the adenoma detection rates and adenoma miss rate of the retroflexed-view versus forward-view examination of the right colon. Results: Of the 200 enrolled patients, retroflexion was successful in 182 (91%). Forward-view examination of the right colon detected 88 polyps, of which 66 were adenomas yielding a polyp and adenoma detection rates of 25.5% and 19%, respectively. Additionally, retroflexion detected a further 30 polyps of which 23 were adenomas, accordingly improving the polyp and adenoma detection rates to 29.5% and 25%, respectively. Furthermore, the polyp and adenoma miss rate in the right colon was 24.1% and 25.8% respectively. Conclusion: Colonoscopy with right-sided retroflexion after forward-view examination significantly increases the detection of adenomas compared with standard forward-view examination with a high success rate and small risk of adverse events.